Pengaruh Preeklamsia dan Hipertensi Kronis terhadap Kejadian Bayi Kecil Masa Kehamilan (KMK) - Irmitasari Irmitasari; Detty Siti Nurdiati; Diah Rumekti Hadiati (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: Preeclampsia and chronic hypertension are associated with a large number of cases of small infants during pregnancy (SIP) and perinatal deaths. There are conflicting inconsistencies between research on the effect of preeclampsia and chronic hypertension on KMK. The data showed that preeclampsia had a very significant effect on the occurrence of KMK, but in reality not all infants of preeclampsia mothers gave birth to babies with KMK. This raises the assumption that there are other factors that inhibit the influence of preeclampsia and chronic hypertension on birth weight.Objective: to determine the effect of preeclampsia and chronic hypertension on KMK in Dr. Sardjito Yogyakarta.Method: Retrospective cohort. Data of maternity patients with preeclampsia, maternity patients with chronic hypertension, and weight data of babies born at RSUP Dr. Sardjito were recorded. Also noted parity, maternal age, employment and education. Data were taken from medical records and classified into normotension, preeclampsia, and chronic hypertension using consecutive sampling methods.Result and Discussion: There were 81 samples for each normotension group, preeclampsia, and chronic hypertension. Preeclampsia is significantly at risk of experiencing SIP 7,43 times (95% IK 3,13-17,66). Chronic hypertension is significantly at risk of experiencing 5,15 times SIP% IK 2,15-12,36). Multigravida subjects were at risk of experiencing SIP 1,92 times (IK 95% 1,04-3,55) There was no significant difference in the proportion of SIP in subjects based on age, occupation, and education.Conclusion: Preeclampsia, chronic hypertension, and multigravida parity significantly provide a higher risk of the incidence of SIP. If the three factors work together, they will reinforce the effect on increasing the risk of SIP.Keywords: Small gestational period; preeclampsia; chronic hypertension